Investigating hip muscles function in subtrochanteric fracture stabilized with dynamic condyle screw versus proximal femoral nail anti-rotation - Seyed Mehdi Hosseini Khameneh; Sona Bonakdar; Fatemeh Abbasi; Amirhossein Salmannezhad; Amin Alizadeh; Morteza Gholipour (Journal of Orthopaedic Reports)
Aims and objectives: Weakness of the abductor muscles in subtrochanteric fractures is often overlooked, leading to decreased patient function. The aim of this study was to compare the results of abductor muscles function in subtrochanteric fracture stabilized with dynamic condyle screw (DCS) versus proximal femoral nail anti-rotation (PFNA). Materials and methods: In a retrospective cohort study, 103 patients aged 20–60 years with subtrochanteric fractures who were admitted to the hospital from December 2018 to December 2021, were divided into two groups: PFNA (56 patients) and DCS (47 patients). Patients were evaluated and compared at three months and six months after the surgery in terms of Harris hip score (HHS), Modified McKay criteria (MMc), pain score (VAS), Muscular power test and Trendelenburg test. Results: The mean HHS between the two groups (PFNA vs DCS) was (80.17±7.11 vs 76.17±8.12) at the first follow-up and (84.39±7.85 vs 83.97±12.5) at the second follow-up, respectively. Despite the higher HHS score in the PFNA group at three and six months, this difference was not significant (P1 = 0.72, P2 = 0.731). MMc has been improved at the second follow-up with a higher number of patients in Excellent and lower numbers in Fair and Poor. However, statistics showed no significant difference between the groups at two follow-ups. There was not any statistically significant difference between the patients in the two groups in terms of pain scores in follow-ups (P1 = 0.443, P2 = 0.948). Muscle power grade had no significant difference between the groups. Also, the decrease in Trendelenburg test (normal to severe) in the third month in the PFNA group was less than in the DCS group (P1 = 0.031), but there was no significant difference between the groups after 6 months (P2 = 0.595). Conclusion: According to our study, regardless of the type of fixation device, they had good functional and clinical results during six months. Therefore, following up patients in regular periods after surgery and paying attention to the clinical function of the abductor muscles is important, which can be improved by targeted physiotherapy.